MEAT CONSUMPTION AS AN INDICATOR OF ECONOMIC WELL-BEING — CASE STUDY OF A DEVELOPED AND DEVELOPING ECONOMY - Joanna Bereżnicka; Tomasz Pawlonka (Acta Scientiarum Polonorum. Oeconomia, 2018)
The aim of the study was to verify the criterion of meat consumption as a marker of economic well-being, in economies at different phases of development. Meat consumption per capita is a widely used variable which is used to indicate the economic bases for the exclusion of meat and meat products from the diet. The study was performed simultaneously in Austria (a developed country) and Poland (a developing country) in 2015. Descriptive statistics, econometric and descriptive models were used to process the research material. Respondents were classified according to the wealth criterion, measured by the average income per household member in a given country. In the case of the developing economy, it was discovered that the meat consumption function takes the shape of an indifference curve. In the developed economy, once the income per household member exceeds 157% of the average national income, consumers exclude meat and other meat products from their diet for health reasons and reservations concerning the quality and origin of the meat. The consumption of meat in Poland is determined by income amount, at a greater degree than in a developed economy. Low income in Polish families is the reason for the exclusion of meat consumption.